Copper Benzene‐1,3,5‐Tricarboxylate Metal‐Organic Framework Performance as a Heterogeneous Catalyst for Biodiesel Production - Jason Ik C. Lau; Sabeeha N. B. A. Khadaroo; Jiuan J. Chew; Deni S. Khaerudini; Agus Saptoro; Jaka Sunarso (Energy Science & Engineering)
ABSTRACT The increasing demand for sustainable fuels has driven extensive research into biodiesel production, which typically relies on the use of active catalysts to facilitate the transesterification of oils. While homogeneous catalysts are commonly employed, they pose challenges in terms of recyclability and environmental impact, leading to growing interest in heterogeneous catalysts. Among these, metal‐organic frameworks (MOFs) have gained attention due to their high surface area and tuneable properties. This study investigates the performance of a copper benzene‐1,3,5‐tricarboxylate (CuBTC) MOF as an effective heterogeneous catalyst for biodiesel production. CuBTC was synthesised via solvothermal method and thoroughly characterised using scanning electron microscopy to examine the morphology, powder X‐ray diffraction to determine the crystalline structure, and Fourier transform infrared spectroscopy to identify the functional groups. The synthesised CuBTC has an octahedral morphology and successfully catalysed biodiesel production with unsaturated fatty acids within the C16 to C18 range, achieving a yield of 78.6% using 1 wt.% CuBTC and a 10:1 methanol‐to‐oil molar ratio. The iodine value of the produced biodiesel was 59.3 g I/g, and the higher heating value was 39.2 MJ/kg. Recycled CuBTC maintained its efficacy, yielding 76.6% and 63.4% fatty acid methyl esters in the first and second recycling runs, respectively, with 16.6% and 15.3% of C16 to C18 fatty acids. The produced biodiesel met quality standards outlined in EN 14214, highlighting CuBTC's potential for sustainable biodiesel production.